ARTIFICIAL INTELLIGENCE-BASED METHODS FOR EARLY DISEASE DIAGNOSIS (Modern education and development, 2025)
Over the past decade, Artificial Intelligence (AI) technologies have brought revolutionary changes to the field of medicine. Early disease detection is one of the top priorities in healthcare, playing a crucial role in improving treatment effectiveness and prolonging patient survival. Traditional diagnostic methods often require significant time, are subject to human interpretation, and in some cases, increase the risk of late detection. For this reason, AI-powered automated early diagnosis systems have gained considerable scientific and practical attention in recent years. These systems analyze vast amounts of medical data — including X-ray images, MRI scans, genetic information, and laboratory results — to identify complex patterns that may be beyond human perception or experience.